Young Fu of the upper Yangtze - Lewis, Elizabeth Foreman 1892-1958 (Henry Holt, 2007)
In the 1920's, a Chinese youth from the country comes to Chungking with his mother where the bustling city offers adventure and his apprenticeship to a coppersmith brings good fortune.